PARENT-CHILD COMMUNICATION STRATEGIES IN THE DIGITAL ERA: A COUNSELING APPROACH TO REDUCE SCREEN TIME AND STRENGTHEN THE BONDS - Permana, Hara; Sulistianingsih, Sulistianingsih; Muslimah, Muslimah; Fitriyanti, Elvira (Sekolah Tinggi Agama Islam Kuningan, 2024)
The background of this research focuses on increasing use digital devices by children in the digital era, which has an impact negative on interaction family and development social child . Use excessive technology​ reduce quality communication between parents and children , so​ effective strategies are needed to reduce time screen and strengthen bond emotional in the family . The purpose of this study was to develop and test communication strategies based on counseling that can be used by parents to reduce dependence children on digital devices as well repair quality interactions within the family . This study uses approach qualitative with method studies case . Data collected through interview in-depth and observation participatory against 10 families who have child Age 7-12 years . Counseling techniques applied during four week to reduce time screen children and strengthen communication in the family . The results of the study showed that after follow session counseling , average time screen child decrease up to 25%. In addition , parents report existence improvement quality communication and bonding emotional with children them . This finding confirms that approach counseling based on effective interpersonal communication in dealing with challenge use technology overused by children.